Adjacent Cell Marker Lateral Spillover Compensation and Reinforcement for Multiplexed Images - Bai, Yunhao; Zhu, Bokai; Rovira-Clave, Xavier; Chen, Han; Markovic, Maxim; Chan, Chi Ngai; Su, Tung-Hung; McIlwain, David R.; Estes, Jacob D.; Keren, Leeat; Nolan, Garry P.; Jiang, Sizun (Frontiers in Immunology, 2021)
Multiplex imaging technologies are now routinely capable of measuring more than 40 antibody-labeled parameters in single cells. However, lateral spillage of signals in densely packed tissues presents an obstacle to the assignment of high-dimensional spatial features to individual cells for accurate cell-type annotation. We devised a method to correct for lateral spillage of cell- surface markers between adjacent cells termed REinforcement Dynamic Spillover EliminAtion (REDSEA). The use of REDSEA decreased contaminating signals from neighboring cells. It improved the recovery of marker signals across both isotopic (i.e., Multiplexed Ion Beam Imaging) and immunofluorescent (i.e., Cyclic Immunofluorescence) multiplexed images resulting in a marked improvement in cell-type classification.